The management of the community based tourism in Thailand: an evaluation of its performance - Jitpakdee, Pit (2019)
Community based tourism (CBT) is a type of tourism that is organized, operated and managed by members of the local communities in order to develop and increase the local community’s income, in addition to sustain the CBT management in the longrun. This study aims to provide information for the CBT communities in Thailand on the current status of the CBT management performance, and identify the management factors that would influence CBT management performance. This study also aims to propose a new CBT guideline for the CBT in Thailand. Data was collected by employing questionnaires formulated through the concept of the Context, Input, Process and Product (CIPP) model for evaluation to the local members of the CBT communities who participated in the CBT management. In addition, in-depth interviews were also employed with the local leaders of the CBT members and the representatives of the local administrative organizations in the same area of the communities. Data was analyzed using the Statistical Package for Social Science (SPSS) to acquire the results. The findings provide significant information on the current CBT management performance of the local communities, and the factors that influence the management performance which could be used to form mathematical equations which acts as a new guideline for the CBT members. It is suggested that the local members who are involved in the CBT should emphasize more on the key factors which are human resource management, the laws, rules and agreements, the operational plans and guidelines, tourism activities, the fairdistributed income system, the safety and security, and the environmental management in order to increase the CBT management performance which could lead to the sustainability of the local communities in Thailand.